2022
DOI: 10.3892/or.2022.8292
|View full text |Cite
|
Sign up to set email alerts
|

Significance of cancer stroma for bone destruction in oral squamous cell carcinoma using different cancer stroma subtypes

Abstract: Stromal cells in the tumor microenvironment (TME) can regulate the progression of numerous types of cancer; however, the bone invasion of oral squamous cell carcinoma (OSCC) has been poorly investigated. In the present study, the effect of verrucous SCC-associated stromal cells (VSCC-SCs), SCC-associated stromal cells (SCC-SCs) and human dermal fibroblasts on bone resorption and the activation of HSC-3 osteoclasts in vivo were examined by hematoxylin and eosin, AE1/3 (pan-cytokeratin) and tartrate-resistant ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 60 publications
(63 reference statements)
0
12
0
Order By: Relevance
“…However, the effects of different properties of the normal stroma on bone resorption have not yet been fully elucidated. Our previous studies assessed the effect of different subtypes of cancer stroma on bone invasion of both HSC-2 and HSC-3 cells (20)(21)(22). Furthermore, our previous study also assayed the effects of normal stroma G-SCs and P-SCs on bone invasion of OSCC but did not provide a detailed description of the bone invasion type and potential regulatory mechanism (5).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the effects of different properties of the normal stroma on bone resorption have not yet been fully elucidated. Our previous studies assessed the effect of different subtypes of cancer stroma on bone invasion of both HSC-2 and HSC-3 cells (20)(21)(22). Furthermore, our previous study also assayed the effects of normal stroma G-SCs and P-SCs on bone invasion of OSCC but did not provide a detailed description of the bone invasion type and potential regulatory mechanism (5).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies on the tumor stroma have only reported that the cancer parenchyma subordinately dominates the stroma and contributes to the progression of cancerous tissue (18,19); therefore, the mechanisms underlying the effect of the cancer stroma on the parenchyma are not clear. Our previous studies reported that the cancer stroma regulates bone invasion of human OSCC cell lines, HSC-2 and HSC-3 cells (20)(21)(22)(23). Therefore, not only gingival cancer but also tongue cancer induces bone invasion.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations